ASBĀB AL-NUZŪL: METHODS AND ITS APPLICATION TO VERSES OF THE QUR’AN - Muna, Rozatul; Mahdi, M. Fakhrul (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2021)
The study of asbāb al-nuzūl is an essential instrument in understanding the historical context in the Al-Qur’an. This study aimed to examine the background of the revelation of the verses of the Al-Qur’an. Moreover, it was also very helpful to find out the meaning of the verse to understand the Qur’anfor different times and places. This study employed qualitative research, which referred to library research by examining relevant theories and texts. This study examined the two rules caused by differences of opinion among scholars. The two rules become ibarah (handles); namely, the pronunciation generality is not a specific cause, and a specific cause is not a pronunciation generality.